2019
DOI: 10.1186/s13567-019-0634-2
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lymphocyte apoptosis in spleen by CXCL13 after porcine circovirus type 2 infection and regulatory mechanism of CXCL13 expression in pigs

Abstract: Porcine circovirus-associated disease (PCVAD) is one of the most serious infectious diseases in pigs worldwide. The primary causative agent of PCVAD is porcine circovirus type 2 (PCV2), which can cause lymphoid depletion and immunosuppression in pigs. Our previous study demonstrated that Laiwu (LW) pigs, a Chinese indigenous pig breed, have stronger resistance to PCV2 infection than Yorkshire × Landrace (YL) pigs. In this study, we found that the YL pigs showed more severe lymphocyte apoptosis and higher viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…In this study, KM mice infected with PCV2 showed signs of lung interstitial pneumonia, partial lymphocyte loss and macrophage in ltration in the spleen and the expression of Cap gene were higest in the liver. This conclusion is consistent with previous reports [24] in which piglets infected with PCV2 could cause lymphocyte loss and monocytes in ltration, it is also consistent with the Pathological results of spleen HE in PCV2 infected laiwu pigs (LW) and Yorkshire pigs (YL) [25]. Some researchers demonstarated that the typical symptoms of interstitial pneumonia was observed in piglets [26] and KM mice [22] infected with PCV2, our nding is consistent with the reports mentioned above.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, KM mice infected with PCV2 showed signs of lung interstitial pneumonia, partial lymphocyte loss and macrophage in ltration in the spleen and the expression of Cap gene were higest in the liver. This conclusion is consistent with previous reports [24] in which piglets infected with PCV2 could cause lymphocyte loss and monocytes in ltration, it is also consistent with the Pathological results of spleen HE in PCV2 infected laiwu pigs (LW) and Yorkshire pigs (YL) [25]. Some researchers demonstarated that the typical symptoms of interstitial pneumonia was observed in piglets [26] and KM mice [22] infected with PCV2, our nding is consistent with the reports mentioned above.…”
Section: Discussionsupporting
confidence: 93%
“…Based on previous reports, lymphocyte depletion and apoptosis in lymphoid tissues are histological hallmarks in PCV2-infected pigs [54][55][56]. Interestingly, these histopathological lesions are similar to Marek's disease and African swine fever [57,58].…”
Section: Discussionmentioning
confidence: 69%
“…However, due to slow growth and a low percentage of lean meat, many indigenous pig breeds have been replaced by introduced pig breeds, including the Landrace, Duroc, and Yorkshire. Some Chinese pig breeds have become useful resources for academic research, including the Wuzhishan pig (Xu et al, 2019), Laiwu pig (Liu et al, 2019), Tibetan pig (Zhang et al, 2019), Taihu pig , and the Min pig (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%